Influence of an information system in the control of incidents of school bullying (LACCEI, 2024)
School violence or bullying can be reported by students through an incident logbook, but this process is not widely known or is avoided out of embarrassment. Additionally, the paper record is susceptible to loss or damage. For this reason, an investigation was carried out to develop an incident management system for an educational institution, with the aim of recording and controlling incidents of school violence. The process began with the awareness of teachers about its importance and continued with the implementation of the software, finally the system was implemented for end users, including administrators, teachers and students. As a result, it was found that the information system had a positive impact on incident control, increasing the number of incidents attended by 50% and optimizing time by 40.42% for the registration and treatment of new incidents.